Value-Based Higher Education Innovation Model: A Theoretical Foundation - Nur Balqishanis, Zainal Abidin; M. R., Abdul Hamid (Medwell Journals, 2017)
Innovation plays an important role in the development of any organization including higher education institutions (HEIs) that forced many to embark this issue. HEIs should be the role model in the practice of innovation so as to encourage and empower innovation for the survival of research institution. Therefore, this article expounded the critical factors that are crucial for achieving innovation excellence in an organization based on the theories integrated (resource-based view, total quality management and stakeholder theory). Five factors namely objectives and strategies, change management, resource management, best practices and innovation have been identified as an enabling factor in organizational innovation excellence. In addition, the intangibles criteria of those critical factors i.e. the core values that support each factor are also discussed. The proposed Malaysian higher education innovation model that integrates all five critical factors is also introduced. Through the proposed model, it could be the basis for HEIs especially in Malaysia to accelerate their innovative capability by garnering all the efforts and endeavor for achieving excellence and be recognized institutions worldwide.